1999
DOI: 10.1259/bjr.72.853.10341683
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic detection and characterization of musculoskeletal and subcutaneous tissue abnormalities in sickle cell disease.

Abstract: Pain due to bone marrow infarction is common in homozygous sickle cell disease (SS disease). Musculoskeletal pathology may be responsible for persistent atypical symptoms. We have assessed the frequency and ultrasound appearances of soft tissue and joint abnormalities in SS disease. SS disease patients with atypical musculoskeletal symptoms were examined with ultrasound over a 2 year period. Ultrasound findings were correlated with those at surgery or percutaneous drainage. 31 episodes in 23 patients were refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
2
12
1
Order By: Relevance
“…6 Sidhu and Rich described a subperiosteal abscess as a hypoechoic collection with its base adjacent to a bone, without intervening soft tissue, extending into the surrounding muscle, representing an inflammatory exudate dissecting in a subperiosteal plane. 5 Our case fits this description in the setting of SCD and especially with abnormal inflammatory parameters. However, our patient also had abnormal color flow signal from a cortical vessel.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…6 Sidhu and Rich described a subperiosteal abscess as a hypoechoic collection with its base adjacent to a bone, without intervening soft tissue, extending into the surrounding muscle, representing an inflammatory exudate dissecting in a subperiosteal plane. 5 Our case fits this description in the setting of SCD and especially with abnormal inflammatory parameters. However, our patient also had abnormal color flow signal from a cortical vessel.…”
Section: Discussionsupporting
confidence: 82%
“…1 One of the reasons for the high frequency of infection in patients with SCD could be the reduced immuno-competence related to sludging of distorted red blood cells in the spleen. 5 Hyposplenism secondary to infarction and subsequent fibrosis is also an important factor, as are impaired phagocytosis and complement dysfunction. 6 Sidhu and Rich described a subperiosteal abscess as a hypoechoic collection with its base adjacent to a bone, without intervening soft tissue, extending into the surrounding muscle, representing an inflammatory exudate dissecting in a subperiosteal plane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonography shows the extraosseous pathology in acute osteomyelitis and may show periosteal elevation (William et al, 2000). It has also the advantage of being rapid, non-invasive and fairly simple to target to the area(s) of maximum pain (Sidhu & Rich, 1999). The sensitivity of ultrasonography in diagnosing osteomyelitis in sickle cell disease has been reported to be as high as 74% (Rifai & Nyman, 1997;Sadat-Ali et al, 1998;William et al, 2000;Riebel et al, 2003).…”
Section: Diagnosis Of Osteomyelitis In Sickle Cell Diseasementioning
confidence: 99%
“…9,[12][13][14] Numerous studies have used ultrasound to described a range of superficial focal and diffuse skin appearances including tumour, lipoma, haematoma, lymphoma, abscess, cellulitis and panniculitis. 9,10,13- 16 We used ultrasound to investigate subcutaneous appearances in people using apomorphine infusions and found that in every case the infusion sites had markedly abnormal sonographic appearances compared to control areas.…”
Section: Discussionmentioning
confidence: 99%